The Impacts of East China Sea Kuroshio Front on Winter Heavy Precipitation Events in Southern China. Issue 4 (9th February 2023) - Bai, HaoKun; Hu, HaiBo; Ren, Xuejuan; Yang, Xiu‐Qun; Zhang, Yang; Mao, Kefeng; Zhao, Yihang
Abstract: The wintertime Kuroshio sea surface temperature (SST) front has the significant climate effects on Southern China. The study demonstrates a close relationship between heavy precipitation over Southern China and Kuroshio SST front in winter. More than half winter heavy rainfall events in Southern China are proved to be resulted from strong High‐frequency Variability events of the sea surface Wind Coupled with Precipitation (HV‐WCP events) over Kuroshio SST front. One day before strong HV‐WCP events, the initial precipitation appears over Middle‐lower Yangtze River due to the significantly enhanced frontal intensity. Then, precipitation generates low‐level cyclone and southeasterly wind anomalies, after it moving into Kuroshio front area because of the winter monsoon. The significant marine atmospheric boundary layer (MABL) height gradient over Kuroshio leads to plentiful moisture transporting from MABL into the free atmosphere and enhances the local precipitation again. This process further causes the large‐scale stratus rainband extending to Southern China and enhancing the heavy rainfall locally. Especially in 2008 winter, several processes of a strong HV‐WCP event followed by continuous weak ones are conducive to the low‐temperature‐precipitation disaster in Southern China. Plain Language Summary: The wintertime Kuroshio sea surface temperature front in the East China Sea is turned out to be relevant with the heavy precipitation in Southern China significantly. The strong HV‐WCP events over Kuroshio front area, defined as the High‐frequency Variability events of the sea surface Wind Coupled with Precipitation, determine more than half winter heavy precipitation events in Southern China. Due to the significantly enhanced frontal intensity on the day before strong HV‐WCP events, the initial precipitation appears in Middle‐lower Yangtze River. After it moving to the Kuroshio front, the positive feedback between circulation, vapor transport, and rainfall makes precipitation enhanced over Kuroshio front. Moreover, this positive feedback causes a large‐scale stratus precipitation band extending to the Southern China and strengthening the heavy rainfall there. Further results suggest that, on the interannual scale, the more C‐events defined as a strong HV‐WCP event followed by continuous weak ones over Kuroshio lead to more continuous low‐temperature‐precipitation winter days in Southern China, typically for the severe disaster period in 2008 early winter. Therefore, the HV‐WCP events over Kuroshio front have potential prediction significance on persistent winter disasters in Southern China, which can be used to prevent social damages caused by the extreme synoptic events. Key Points: The high‐frequency wind‐coupled‐precipitation events over East China Sea contribute more than half winter heavy‐rainy days in Southern China The vapor sources of most winter heavy precipitation in Southern China are observed cross boundary layer from warm flank of Kuroshio front The winter low‐temperature‐precipitation disasters in Southern China are revealed to be connected with the special aforementioned events